Survival impact of histological response to neoadjuvant chemotherapy according to number of cycles in patients with advanced ovarian cancer. Issue 8 (20th July 2022) - Betrian, Sarah; Angeles, Martina Aida; Gil Moreno, Antonio; Cabarrou, Bastien; Deslandres, Marion; Ferron, Gwenael; Mery, Eliane; Floquet, Anne; Guyon, Frederic; Pérez-Benavente, Assumpció; Spagnolo, Emanuela; Rychlik, Agnieszka; et al.
Abstract : Objective: We sought to evaluate the impact of chemotherapy response score according to the number of cycles of neoadjuvant chemotherapy, on disease-free survival and overall survival, in patients with advanced epithelial ovarian cancer ineligible for primary debulking surgery. Methods: This multicenter retrospective study included patients with International Federation of Gynecology and Obstetrics (FIGO) stage IIIC-IV epithelial ovarian cancer who underwent 3–4 or 6 cycles of a platinum and taxane-based neoadjuvant chemotherapy, followed by complete cytoreduction surgery (CC-0) or cytoreduction to minimal residual disease (CC-1), between January 2008 and December 2015, in four institutions. Disease-free survival and overall survival were assessed according to the histological response to chemotherapy defined by the validated chemotherapy response score. Results: A total of 365 patients were included: 219 (60.0%) received 3–4 cycles of neoadjuvant chemotherapy, and 146 (40.0%) had 6 cycles of neoadjuvant chemotherapy before cytoreductive surgery. There were no significant differences in early relapses, disease-free survival, and overall survival according to the number of neoadjuvant chemotherapy cycles. However, regardless of the number cycles of neoadjuvant chemotherapy, persistent extensive histological disease (chemotherapy response score 1–2) was significantly associated with a higher peritoneal cancer index, minimal residual disease (CC-1), and early relapses. Median disease-free survival in patients with complete or near-complete response (score 3) was 28.3 months (95% CI 21.6 to 36.8), whereas it was 16.3 months in patients with chemotherapy response score 1–2 (95% CI 14.7 to 18.0, p<0.001). Conclusion: In our cohort, the number of neoadjuvant chemotherapy cycles was not associated with disease-free survival or overall survival. Chemotherapy response score 3 improved oncological outcome regardless of the number of neoadjuvant chemotherapy cycles.